Hunting with Cane: Traditional Cherokee Blowguns and Darts - Doug Meyer (EXARC, 2013)
The Cherokee Indians were a large Southeastern tribe who occupied land in North Carolina, South Carolina, Georgia, Alabama, Tennessee and Virginia. During the Historic Period, the Cherokee were one of the Five Civilized Tribes and even had their own writing system developed by Sequoyah. When gold was discovered in Cherokee occupied lands, the Cherokee were forced to relocate to a reservation in Oklahoma. A group of ‘renegade’ Cherokee under Tsali hid in the mountains of North Carolina and refused to go on the Trail of Tears to Oklahoma. Tsali’s death paved the way for the Qualla Boundary or Eastern Cherokee Reservation to be formed in the North Carolina Mountains. The surviving Cherokee from the Trail of Tears set up the Western Cherokee Reservation in Oklahoma. Although I have visited the reservation in Oklahoma, I have spent more time with the Cherokees on the Qualla Boundary in North Carolina (Woodward 1963).